2015
DOI: 10.1530/erc-15-0209
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the androgen receptor in bladder cancer

Abstract: Men are three to four times more likely to get bladder cancer than women. The gender disparity characterizing bladder cancer diagnoses has been investigated. One hypothesis is that androgen receptor (AR) signaling is involved in the etiology and progression of this disease. Although bladder cancer is not typically described as an endocrine-related malignancy, it has become increasingly clear that AR signaling plays a role in bladder tumors. This review summarizes current findings regarding the role of the AR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 94 publications
(130 reference statements)
0
45
0
Order By: Relevance
“…A variety of experimentally validated target genes regulated by hsa-miR-31-5p has been described in different tumor types [26], including AR and DNMT3A genes. The androgen receptor (AR) is a critical transcription factor with prognostic value in breast cancer and prostate [28, 29] as well as in bladder carcinomas [30]. …”
Section: Discussionmentioning
confidence: 99%
“…A variety of experimentally validated target genes regulated by hsa-miR-31-5p has been described in different tumor types [26], including AR and DNMT3A genes. The androgen receptor (AR) is a critical transcription factor with prognostic value in breast cancer and prostate [28, 29] as well as in bladder carcinomas [30]. …”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, it mediates physiological activities by binding to androgen. It has been demonstrated that androgen signaling has been linked to regulation of proliferation, motility and cell death in urinary malignancies (28,29). Importantly, it has essential roles in malignancies of the prostate, bladder, kidney, lung, breast and liver (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that AR plays a crucial role in malignancies of the prostate, kidney, breast and bladder cancers [17]. In bladder cancer, high expression of AR has been observed and positively correlated with disease progression [18].…”
Section: Introductionmentioning
confidence: 99%
“…In bladder cancer, high expression of AR has been observed and positively correlated with disease progression [18]. Moreover, AR signaling may also contribute to invasion and metastasis of bladder cancer [17]. …”
Section: Introductionmentioning
confidence: 99%